Joule‐Thomson Cooling During CO2 Injection Under Unsteady‐State Delayed Heat Exchange - Christina Chesnokov; Kofi Ohemeng Kyei Prempeh; Rouhi Farajzadeh; Pavel Bedrikovetsky (Water Resources Research)
Abstract Joule‐Thomson cooling during CO2 injection into low‐pressure fields can lead to injectivity impairment due to hydrate formation. This paper presents axial‐symmetric flow model, which can be used to predict propagation of temperature and CO2 fronts during CO2 injection into porous formations accounting for Joule‐Thomson cooling and unsteady‐state delayed heat exchange between the reservoir and the adjacent formations. The solution of the 1D flow is validated by comparing with the quasi 2D analytical heat‐conductivity solution. The non‐steady state heat exchange results in a temperature front that propagates without limit into the reservoir with time. The temperature profiles exhibit a temperature decrease from the injected temperature to a minimum value, followed by a sharp increase to initial reservoir temperature on the temperature front. The solution allows plotting temperature‐pressure (T‐P) profiles at fixed moments in the CO2‐water phase diagram. By changing injection parameters such as injection rate, the T‐P trajectories allow for assessment of hydrate formation.